Xanthones from Swertia mussotii and Their α-Glycosidase Inhibitory Activities - Luo, Cui-Ting; Zheng, Huan-huan; Mao, Shuang-Shuang; Yang, Mao-xun; Luo, Cheng; Chen, Heru (Planta Medica, 2014)
Two new xanthones, 1,8-dihydroxy-3-methoxyxanthone 7-O-[α-L-rhamnopyranosyl(1 → 2)-β-D-glucopyranoside] (1) and 1,8- dihydroxy-3-methoxyxanthone 7-O-[α-L-rhamnopyranosyl(1 → 3)-α-L-rhamno-pyranosyl (1 → 2)-β-D-xylopyranoside] (2), together with 26 known xanthones (3–28), were isolated from the aqueous ethanol extract of the traditional Chinese herb Swertia mussotii. Their structures were elucidated via spectroscopic analyses including 2D NMR. The inhibition of α-glucosidase by the isolated xanthones was evaluated by an in vitro high-throughput screening assay. Our results indicated that 1,3,5,8-tetrahydroxyxanthone is the best inhibitor with an IC50 value of 5.33 ± 0.09 µM, while the O-glycosylated xanthones were poor α-glycosidase inhibitors.
Keywords: Gentianaceae; Swertia mussotii; xanthones; α-glucosidase inhibitor; diabetes mellitus